HMGB1 cleavage by complement C1s and its potent anti-inflammatory product - Lorvellec, Marie; Chouquet, Anne; Koch, Jonas; Bally, Isabelle; Signor, Luca; Vigne, Jeanne; Dalonneau, Fabien; Thielens, Nicole M.; Rabilloud, Thierry; Dalzon, Bastien; Rossi, Véronique; Gaboriaud, Christine (Frontiers in Immunology, 2023)
Complement C1s association with the pathogenesis of several diseases cannot be simply explained only by considering its main role in activating the complement classical pathway. This suggests that non-canonical functions are to be deciphered for this protease. Here the focus is on C1s cleavage of HMGB1 as an auxiliary target. HMGB1 is a chromatin non-histone nuclear protein, which exerts in fact multiple functions depending on its location and its post-translational modifications. In the extracellular compartment, HMGB1 can amplify immune and inflammatory responses to danger associated molecular patterns, in health and disease. Among possible regulatory mechanisms, proteolytic processing could be highly relevant for HMGB1 functional modulation. The unique properties of HMGB1 cleavage by C1s are analyzed in details. For example, C1s cannot cleave the HMGB1 A-box fragment, which has been described in the literature as an inhibitor/antagonist of HMGB1. By mass spectrometry, C1s cleavage was experimentally identified to occur after lysine on position 65, 128 and 172 in HMGB1. Compared to previously identified C1s cleavage sites, the ones identified here are uncommon, and their analysis suggests that local conformational changes are required before cleavage at certain positions. This is in line with the observation that HMGB1 cleavage by C1s is far slower when compared to human neutrophil elastase. Recombinant expression of cleavage fragments and site-directed mutagenesis were used to confirm these results and to explore how the output of C1s cleavage on HMGB1 is finely modulated by the molecular environment. Furthermore, knowing the antagonist effect of the isolated recombinant A-box subdomain in several pathophysiological contexts, we wondered if C1s cleavage could generate natural antagonist fragments. As a functional readout, IL-6 secretion following moderate LPS activation of RAW264.7 macrophage was investigated, using LPS alone or in complex with HMGB1 or some recombinant fragments. This study revealed that a N-terminal fragment released by C1s cleavage bears stronger antagonist properties as compared to the A-box, which was not expected. We discuss how this fragment could provide a potent brake for the inflammatory process, opening the way to dampen inflammation.